Organic-walled tentaculids of Late Devonian (Frasnian) deposits of the Appalachian and Michigan Basins, Laurussia (NY, MI, OH) - Kimberly C. Meehan; James T. Boyle (Geologica Acta, 2022)
This is the first report of organic-walled tentaculid remains from Givetian through Frasnian age deposits of the Michigan and Appalachian Basins in western Laurussia. This adds to the geographic scope of similar finds that have been described from the Frasnian through the Famennian in eastern Laurussia. However, those previous specimens were retrieved through palynological preparations and more closely resemble sheath structures rather than the full forms found herein, which were retrieved through complete maceration with ammonium surfactants.